Eculizumab as a New Treatment for Severe Acute Post-infectious Glomerulonephritis: Two Case Reports - Chehade, Hassib; Guzzo, Gabriella; Cachat, Francois; Rotman, Samuel; Teta, Daniel; Pantaleo, Giuseppe; Sadallah, Salima; Sharma, Amita; Rosales, Ivy A.; Tolkoff-Rubin, Nina; Pascual, Manuel (Frontiers in Medicine, 2021)
Acute post-infections glomerulonephritis (APIGN) is a frequent cause of glomerulonephritis and represents the most common cause of acute glomerulonephritis in children. It can evolve to severe acute renal failure and chronic kidney disease or even end-stage kidney disease. The precise pathophysiological mechanisms of APIGN are still incompletely understood. The implication of the alternative complement pathway and the potential benefits of C5 blockade have been recently highlighted, in particular in the presence of a C3 Nephritic Factor (C3Nef), anti-Factor B or H autoantibodies. We report two children with severe APIGN, successfully treated with eculizumab. The first patient presented a severe form of APIGN with advanced renal failure and anuria, associated with a decreased level of C3 and an increased level of soluble C5b-9, in the presence of a C3NeF autoantibody. The second case had a severe oliguric APIGN associated with low C3 level. Kidney biopsy confirmed the diagnosis of APIGN in both cases. Eculizumab allowed full renal function recovery and the avoidance of dialysis in both cases. In conclusion, the alternative and terminal complement pathways activation might be common in PIGN, and in severe cases, eculizumab might help.